2010
DOI: 10.31610/zsr/2010.19.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Annotated сhecklist of the freshwater fishes of Iran

Abstract: The confirmed freshwater fishes of Iran comprise 202 species in 104 genera, 28 families, 17 orders and 3 classes found in 19 different basins. There are also 23 species whose presence in Iranian waters needs confirmation by specimens. The most diverse order is the Cypriniformes with 120 confirmed species (59.4%) followed by Perciformes with 28 species (13.9%), Cyprinodontiformes (10 species, 5.0%), Clupeiformes (9 species, 4.5%), Salmoniformes (7 species, 3.5%), Mugiliformes and Siluriformes each with 6 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 60 publications
1
21
0
2
Order By: Relevance
“…45 Natural alkaloid as well as their synthetic derivatives have proven to have wide range of pharmacological activities including antimicrobial, analgesic and antispasmodic 46 and it was reported that the antioxidant potential of herbal preparations is due to the presence of phenolic compounds. 47 Moreover, it was well reported that ethanol and methanol act as effective solvents for the extraction of antioxidant phenolic compounds 15 and most important groups of natural products include flavonoids are the widespread class of natural phenolic constituents. It was reported that quenching of active oxygen species is due to several flavonoids present in extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Natural alkaloid as well as their synthetic derivatives have proven to have wide range of pharmacological activities including antimicrobial, analgesic and antispasmodic 46 and it was reported that the antioxidant potential of herbal preparations is due to the presence of phenolic compounds. 47 Moreover, it was well reported that ethanol and methanol act as effective solvents for the extraction of antioxidant phenolic compounds 15 and most important groups of natural products include flavonoids are the widespread class of natural phenolic constituents. It was reported that quenching of active oxygen species is due to several flavonoids present in extract.…”
Section: Discussionmentioning
confidence: 99%
“…It was well reported that ethanol and methanol act as effective solvents for the extraction of antioxidant phenolic compounds. 15 So aqueous Ethanolic (30:70) plant extract was prepared and dry leaves were sonicated twice with 10 time’s higher volume of hydro alcohol for 48 hours at room temperature. Then the solution was filtered by Whatman filter paper number 1 and evaporated using rotary evaporator under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Literature records the distribution of brown trout in three basins in Iran ( Abdoli, 2000; Esmaeili et al, 2010 ). The results of our modelling framework highlighted these basins as the major area of distribution as most occurrences were predicted there.…”
Section: Discussionmentioning
confidence: 99%
“…The country lies in the Palearctic zoogeographical realm bordering the Oriental and African ones ( Coad and Vilenkin, 2004 ), and features a great diversity of aquatic species. Overall, the ichthyofauna of Iran comprises a total of 203 species (180 native of which 40 are endemic and 23 exotic species) ( Esmaeili et al, 2010; Teimori et al, 2012 ). Freshwaters are already exposed to numerous anthropogenic stressors, and are naturally fragmented in stream networks or intermittent water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…A single species, Syngnathus caspius Eichwald, 1831 is found in the Caspian Sea basin and Coad (1985, 1998), Coad and Abdoli (1996), and Esmaeili et al. (2010) place the species in context with the Iranian ichthyofauna. Eichwald (1831) described it from the Balkhan Bay, Caspian Sea; but also appeared as new in Eichwald (1838).…”
Section: Introductionmentioning
confidence: 99%